Method for preparing multi-scale nano lignin waterproof and oil-proof agent by using alkaline pulping black liquor and application of multi-scale nano lignin waterproof and oil-proof agent
By extracting multi -scale nanoconal granules and starch from the alkaline slurry black liquid, preparing multi -scale nano -wood quality waterproof and oil -proof agent for the surface of the paper surface solves the environmental pollution and relatives of traditional waterproof oil -proof agent Water -based problems have achieved the efficient waterproof, oil -proof and mechanical performance of paper.
Patent Information
- Application Number
- CN202411551863.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-01
AI Technical Summary
In the prior art, traditional fluorine-containing waterproof and oil-proofing agents have problems of environmental pollution and human body harm. The hydrophilicity and hygroscopicity of bio-based waterproofing and oil-proofing agents are relatively large, resulting in partial loss of barrier properties under high humidity conditions, and Lignin has been studied as a waterproof and oil-proofing agent.
Extract the multi -scale nanoplin quality particles through the alkaline -made pulp black solution, use the acid precipitation method to prepare, and reproduce it with starch to make multi -scale nanoconal water quality waterproof and oil -proof agent. Essence
It significantly improves the waterproof, oil -proof and mechanical properties of paper, reduces the pore rate, achieves non -toxic and degradable environmental protection effects, and has a wide range of raw materials, simple preparation methods, and low cost.
Smart Images

Figure CN119372948A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of bio-based water-proof and oil-proof agents, and more specifically, relates to a method for preparing a multi-scale nano-lignin water-proof and oil-proof agent by utilizing alkaline pulping black liquor and its application. Background Art
[0002] In some application fields where paper is used as the substrate, it is often necessary to give paper barrier properties due to its insufficient barrier properties to water, air, grease, etc. The commonly used method is to use paper waterproof and oil-proof agents to penetrate internally to fill the capillary holes, or to reduce its interfacial energy through surface treatment. However, traditional fluorine-containing waterproof and oil-proof agents use the special surface energy of fluorine materials to prevent water and grease from penetrating. They are highly persistent and bioaccumulative in the environment, and can cause harm to the human body.
[0003] At present, there are many studies on the preparation of non-toxic and environmentally friendly new waterproof and oil-proof agents using bio-based polymers (such as polysaccharides, proteins, lipids, etc.) as the main raw materials. Bio-based waterproof and oil-proof agents mainly include chitosan, hemicellulose, microfibrillated cellulose and starch. Although these materials are bio-friendly, they still have high hydrophilicity. Films made of these materials are usually hygroscopic, resulting in partial loss of barrier properties under high humidity conditions. Lignin, as a typical biomass macromolecule, is cheap, easy to obtain, environmentally friendly, biodegradable, and has good hydrophobic properties. On the one hand, there are currently few studies on lignin as a waterproof and oil-proof agent for paper. On the other hand, my country's papermaking industry produces a large amount of black liquor every year, which contains a large amount of lignin. According to statistics, more than 95% of lignin is used as waste from pulping and papermaking, and most of it is burned after the alkali recovery process, and has not been well utilized.
[0004] Patent CN 108532362 A provides a method for preparing a lignin sizing agent, but the lignin is modified and then sizing the surface of corrugated paper together with starch, which is complicated to operate and more expensive. It can improve the waterproofness of corrugated paper, but does not provide an oil-proof effect.
[0005] Chinese patent CN 115821628 A discloses a preparation method and application of a cationic starch-based nanocellulose oil-proofing agent, but the process involves three refining processes, which is cumbersome and only has oil-proofing properties.
[0006] Patent CN 105899628 A discloses a lignin-based waterproof coating, which is formed by dissolving lignin in a solvent to form a lignin solution, and coating the lignin solution on a substrate to enhance the waterproofness of the substrate, but does not mention the oil-proof performance.
[0007] Wu Wei's "The Effect of Starch on Water and Oil Resistance of Oil-proof Paper" mentioned that the oil-proof grade can reach level 7 and the water contact angle can reach 90.6° when oxidized starch, cationic starch and cassava starch are mixed with a certain amount of oil-proof agent and polyvinyl alcohol to make a sizing agent for coating oil-proof paper. However, the polyvinyl alcohol in it is a petroleum-based plastic, which is non-renewable, difficult to degrade and has limited oil-proof effect.
[0008] Therefore, it is necessary to develop a new type of non-toxic, harmless, biodegradable, oil-proof and waterproof paper agent with enhanced mechanical properties using lignin extracted from pulping black liquor as raw material, which has important social value. Summary of the invention
[0009] In view of the above problems existing in the prior art, the technical problem to be solved by the present invention is to provide a method for preparing a multi-scale nano-lignin waterproof and oil-proof agent using alkaline pulping black liquor, which has a wide source of raw materials, a simple preparation method and low cost. Another technical problem to be solved by the present invention is to provide a multi-scale nano-lignin waterproof and oil-proof agent prepared by the above method, which can form a dense barrier coating on the surface of paper. Another technical problem to be solved by the present invention is to provide the application of the above multi-scale nano-lignin waterproof and oil-proof agent in the preparation of waterproof and oil-proof paper-based materials.
[0010] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0011] A method for preparing a multi-scale nano-lignin waterproof and oil-proof agent using alkaline pulping black liquor, using alkaline pulping black liquor as raw material, directly preparing multi-scale nano-lignin by acid precipitation method, and compounding the multi-scale nano-lignin with starch to prepare the multi-scale nano-lignin waterproof and oil-proof agent; wherein the particle size of the multi-scale nano-lignin is 200-1500nm.
[0012] Preferably, the specific process of the acid precipitation method is: stirring and heating the alkaline pulping black liquor, adjusting the pH value of the solution with acid, standing and settling, centrifuging and washing to neutrality, freeze drying, grinding, and vacuum drying to obtain multi-scale nano-lignin particles.
[0013] Preferably, the stirring speed is 100-1000 rpm, and the temperature is raised to 20-100°C.
[0014] Preferably, when the pH value of the adjusted solution is between 1 and 5, the acid addition is stopped, and the solution is stirred at the temperature maintained for 30 to 150 minutes.
[0015] Preferably, the acid is selected from any one of sulfuric acid, hydrochloric acid and phosphoric acid.
[0016] Preferably, the starch is selected from any one of surface starch, native starch, oxidized starch and cationic starch.
[0017] Preferably, the mass ratio of the multi-scale nano-lignin to starch is 0.5 to 2:2.
[0018] Preferably, the starch concentration is 5% to 8%.
[0019] The method for preparing a multi-scale nano-lignin water-proof and oil-proof agent using alkaline pulping black liquor specifically comprises the following steps:
[0020] 1) mechanically stirring the alkaline pulping black liquor, adding acid dropwise while stirring until the pH value of the black liquor is 1-5, stopping the acid addition, keeping warm and continuing stirring, standing and settling, centrifugally washing to neutrality, freeze drying, grinding, and vacuum drying to obtain multi-scale nano-lignin particles;
[0021] 2) The multi-scale nano-lignin particles prepared in step 1), starch and purified water are mixed and gelatinized to prepare a multi-scale lignin waterproof and oil-proof agent, and the mixture is kept warm at 60° C. for use.
[0022] The method for preparing a multi-scale nano-lignin waterproof and oil-proof agent by using alkaline pulping black liquor can prepare a multi-scale nano-lignin waterproof and oil-proof agent.
[0023] The multi-scale nano-lignin waterproof and oil-proof agent is used in preparing waterproof and oil-proof paper-based materials.
[0024] The application is prepared by using a rod coater to coat the product with a weight of 80 g / m 2 Double coating is applied on the surface of A4 paper with a coating amount of 5g / m 2 First, apply a layer of multi-scale nano-lignin waterproof and oil-proof agent on the surface of the paper, put the paper with one layer into a constant temperature oven at 60℃ and dry it for 2 minutes, then take it out, apply the second layer of starch, put it into a constant temperature oven at 60℃ and dry it for 5 minutes, and finally balance the treated A4 paper in a constant temperature and humidity chamber for 24 hours.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) The present invention directly extracts nano-lignin particles from alkaline pulping black liquor by acid precipitation, and utilizes the characteristics of nano-materials and the hydrophobicity of lignin itself to compound the nano-lignin with starch to prepare a nano-lignin water-proof and oil-proof agent, and applies sizing on the surface of paper to improve the water-proof and oil-proof properties of the paper;
[0027] (2) The present invention regulates the size of lignin nanoparticles of different sizes to construct a dense multi-level spatial network structure on the surface of paper, thereby improving the water-repellent and oil-repellent properties of paper, reducing the porosity, and thus improving the water-repellent and oil-repellent properties of paper;
[0028] (3) The multi-scale nano-lignin water-proof and oil-proof agent prepared by the present invention is applied to paper-based materials to improve the water-proof and oil-proof properties, and the Cobb 60 value of the original paper can be increased from 62.14 g / m 2 Down to 17.71g / m 2 The Kit value increased from 0 to 10, and the tensile index increased from 41.11Nm / g to 55.96Nm / g, which significantly improved the waterproof, oil-proof and mechanical properties of the paper coating.
[0029] (4) The present invention uses nano-lignin particles extracted from alkaline pulping black liquor as raw materials, which not only has a wide source of raw materials but also can achieve waste recycling and environmental protection, meeting the major strategic needs of sustainable development of my country's materials industry; the preparation method of the present invention is simple, the cost required is low, and has broad industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The infrared spectra of the multi-scale nano-lignin particles prepared in Examples 1-6;
[0031] Figure 2 Particle size scale diagram of the multi-scale nano-lignin particles prepared in Examples 1-6. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described below in conjunction with specific embodiments. In the following examples, unless otherwise specified, the technical means used are conventional means well known to those skilled in the art. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0033] The performance testing method adopted by the present invention is as follows:
[0034] 1. Water resistance test of paper: refer to the determination of water absorption of paper and paperboard GB / T 1540-2002;
[0035] 2. Test on oil resistance of paper: refer to the determination of oil resistance of paper and paperboard GB / T 22805.2-2008;
[0036] 3. Test on the tensile index and elongation of paper: refer to the determination of tensile index of paper and paperboard GB / T453-2002.
[0037] 4. Particle size measurement: Zetasizer Nano-Zs dynamic light scattering nano-laser particle size analyzer, Malvern, UK.
[0038] The alkaline pulping black liquor and native starch used in the following examples were provided by APP Group; the surface starch, oxidized starch and cationic starch were provided by Elkem Silicones (Shanghai) Co., Ltd. The agitator used was a JB300-D electric mechanical agitator purchased from Shanghai Jinmao Industrial Technology Co., Ltd.
[0039] Example 1
[0040] A method for preparing a multi-scale nano-lignin water-proof and oil-proof agent using alkaline pulping black liquor comprises the following steps:
[0041] 1) 500 g of alkaline pulping black liquor was added into a beaker, mechanically stirred at 100 rpm at 20°C, sulfuric acid was added dropwise while stirring until the pH value of the black liquor was 1, then the acid addition was stopped, the mixture was kept warm and stirred for 30 min, and then allowed to stand overnight, centrifuged and washed until neutral, freeze-dried for 48 h, ground, and vacuum-dried at 40°C for 24 h to obtain 24.65 g of multi-scale nano-lignin particles, recorded as L1;
[0042] 2) 0.5 g of the multi-scale nano-lignin particles prepared in step 1), 2 g of surface starch and 23 g of pure water were gelatinized at 90° C. for 1 h to obtain a multi-scale nano-lignin waterproof and oil-proof agent, which was kept warm at 60° C. for use.
[0043] Example 2
[0044] A method for preparing a multi-scale nano-lignin water-proof and oil-proof agent using alkaline pulping black liquor comprises the following steps:
[0045] 1) 500 g of alkaline pulping black liquor was added into a beaker, mechanically stirred at 500 rpm at 60°C, sulfuric acid was added dropwise while stirring until the pH value of the black liquor reached 3, then the acid addition was stopped, the mixture was kept warm and stirred for 90 min, and then allowed to stand overnight, centrifuged and washed until neutral, freeze-dried for 48 h, ground, and vacuum-dried at 40°C for 24 h to obtain 25.89 g of multi-scale nano-lignin particles, recorded as L2;
[0046] 2) 0.5 g of the multi-scale nano-lignin particles prepared in step 1), 2 g of cationic starch and 23 g of pure water were gelatinized at 90° C. for 1 h to obtain a multi-scale nano-lignin waterproof and oil-proof agent, which was kept warm at 60° C. for use.
[0047] Example 3
[0048] A method for preparing a multi-scale nano-lignin water-proof and oil-proof agent using alkaline pulping black liquor comprises the following steps:
[0049] 1) 500 g of alkaline pulping black liquor was added into a beaker, mechanically stirred at 1000 rpm at 100°C, sulfuric acid was added dropwise while stirring until the pH value of the black liquor reached 5, then the acid addition was stopped, the mixture was kept warm and stirred for 150 min, and then allowed to stand overnight, centrifuged and washed until neutral, freeze-dried for 48 h, ground, and vacuum-dried at 40°C for 24 h to obtain 23.11 g of multi-scale nano-lignin particles, recorded as L3;
[0050] 2) 0.5 g of the multi-scale nano-lignin particles prepared in step 1), 2 g of surface starch and 23 g of pure water were gelatinized at 90° C. for 1 h to obtain a multi-scale nano-lignin waterproof and oil-proof agent, which was kept warm at 60° C. for use.
[0051] Example 4
[0052] A method for preparing a multi-scale nano-lignin water-proof and oil-proof agent using alkaline pulping black liquor comprises the following steps:
[0053] 1) 500 g of alkaline pulping black liquor was added into a beaker, mechanically stirred at 100 rpm at 20°C, and nitric acid was added dropwise while stirring until the pH value of the black liquor was 1, then the acid addition was stopped, the mixture was kept warm and stirred for 30 min, and then allowed to stand overnight, centrifuged and washed until neutral, freeze-dried for 48 h, ground, and vacuum-dried at 40°C for 24 h to obtain 22.78 g of multi-scale nano-lignin particles, which were recorded as L4;
[0054] 2) 0.2 g of the multi-scale nano-lignin particles prepared in step 1), 2 g of oxidized starch and 23 g of pure water were gelatinized at 90° C. for 1 h to obtain a multi-scale nano-lignin waterproof and oil-proof agent, which was kept warm at 60° C. for use.
[0055] Example 5
[0056] A method for preparing a multi-scale nano-lignin water-proof and oil-proof agent using alkaline pulping black liquor comprises the following steps:
[0057] 1) 500 g of alkaline pulping black liquor was added into a beaker, mechanically stirred at 100 rpm at 20°C, and phosphoric acid was added dropwise while stirring until the pH value of the black liquor was 1, then the acid addition was stopped, the mixture was kept warm and stirred for 30 min, and then allowed to stand overnight, centrifuged and washed until neutral, freeze-dried for 48 h, ground, and vacuum-dried at 40°C for 24 h to obtain 23.11 g of multi-scale nano-lignin particles, which were recorded as L5;
[0058] 2) 2 g of the multi-scale nano-lignin particles prepared in step 1), 2 g of surface starch and 23 g of pure water were gelatinized at 90° C. for 1 h to obtain a multi-scale nano-lignin waterproof and oil-proof agent, which was kept warm at 60° C. for use.
[0059] Example 6
[0060] A method for preparing a multi-scale nano-lignin water-proof and oil-proof agent using alkaline pulping black liquor comprises the following steps:
[0061] 1) 500 g of alkaline pulping black liquor was added into a beaker, mechanically stirred at 200 rpm at 40°C, and phosphoric acid was added dropwise while stirring until the pH value of the black liquor reached 2, then the acid addition was stopped, the mixture was kept warm and stirred for 60 min, and then allowed to stand overnight, centrifuged and washed until neutral, freeze-dried for 48 h, ground, and vacuum-dried at 40°C for 24 h to obtain 22.02 g of multi-scale nano-lignin particles, which were recorded as L6;
[0062] 2) 0.5 g of the multi-scale nano-lignin particles prepared in step 1), 2 g of native starch and 23 g of pure water were gelatinized at 90° C. for 1 h to obtain a multi-scale nano-lignin waterproof and oil-proof agent, which was kept warm at 60° C. for use.
[0063] Depend on Figure 1 It can be seen that the basic structure of lignin nanoparticles (LNPs) of different sizes has not changed, and the types of functional groups remain consistent. -1 The peaks are relatively scattered, mainly caused by the stretching vibration of CO and the stretching vibration of the secondary structure. -1 The benzene ring CH bending vibration is at 1220cm -1 The stretching vibration of CO in the benzene ring is 1600 cm -1 The position is the stretching vibration of C=C of the benzene ring. 2930cm -1 The absorption peak at 3413 cm is attributed to the CH asymmetric vibration of methyl (-CH3) and methylene (-CH2). -1 The vibration peak of hydroxyl (-OH) is at .
[0064] The particle sizes of the multi-scale nano-lignin particles prepared in Examples 1-6 were measured, and the results are shown in Tables 1 and Figure 2 shown.
[0065]
[0066]
[0067] Comparative Example 1
[0068] Mix 2g of surface starch and 23g of pure water and place in a four-necked flask equipped with an electric stirrer, a condenser and a thermometer, then put into a constant temperature water bath, heat to 90°C for gelatinization reaction for 1h to obtain the surface starch surface sizing agent, and keep warm at 60°C for standby use.
[0069] Comparative Example 2
[0070] Mix 2g of native starch and 23g of pure water and place in a four-necked flask equipped with an electric stirrer, a condenser and a thermometer, then put into a constant temperature water bath, heat to 90°C for gelatinization reaction for 1h to obtain a native starch surface sizing agent, and keep warm at 60°C for standby use.
[0071] Example 7
[0072] 0.1 g of the multi-scale nano-lignin particles prepared in Example 1, 2 g of surface starch and 38 g of pure water were gelatinized at 90° C. for 1 h to obtain a multi-scale nano-lignin waterproof and oil-proof agent, which was kept warm at 60° C. for use.
[0073] Example 8
[0074] Use a rod coater to coat the product at a weight of 80 g / m 2 Double coating is applied on the surface of A4 paper with a coating amount of 5g / m 2 The specific process is: first apply a layer of the test agent on the surface of the paper, put the coated paper into a 60℃ constant temperature oven for 2 minutes and then take it out, apply a second layer of starch, put it into a 60℃ constant temperature oven for 5 minutes, and finally place the treated A4 paper in a constant temperature and humidity room for 24 hours before testing its physical properties.
[0075] The multi-scale nano-lignin water-proof and oil-proof agent prepared in Examples 1-7, the surface starch surface sizing agent prepared in Comparative Example 1, and the native starch surface sizing agent prepared in Comparative Example 2 were coated on the surface of paper by the above method, wherein when two layers of starch were coated, the surface starch was coated in Examples 1-5, 7, and Comparative Example 1, and the native starch was coated in Example 6 and Comparative Example 2. The test results of the paper are shown in Table 2. Among them, the smaller the Cobb 60 value, the better the water-proof property of the paper; the larger the Kit value, the better the oil-proof property of the paper.
[0076] Table 2 Physical properties of coated paper and base paper of Examples 1 to 7 and Comparative Examples 1-2
[0077]
[0078]
[0079] As shown in Table 2, compared with Comparative Example 1, after being coated with the multi-scale nano-lignin water-proof and oil-proof agent prepared by the present invention, the Cobb 60 value of the paper increased from 40.21 g / m 2 Down to 17.71g / m 2, Kit value increased from level 1 to level 10, 41.11Nm / g increased to 55.96Nm / g, and the waterproof, oil-proof and mechanical properties of the paper coating were significantly improved. This shows that nano-lignin itself has hydrophobic properties, and effectively fills and blocks the pores between paper fibers. By compounding with starch and coating on the surface of paper, the pores on the surface of paper are covered, and nano-scale lignin particles construct a micro-nano structure on the surface of paper, forming a dense nano-coating on the surface of paper, which blocks water and grease from penetrating into the interior of the paper.
[0080] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a multi-scale nano-lignin water-proof and oil-proof agent using alkaline pulping black liquor, characterized in that: Alkaline pulping black liquor is used as raw material, multi-scale nano-lignin is directly prepared by acid precipitation method, and the multi-scale nano-lignin is compounded with starch to prepare a multi-scale nano-lignin waterproof and oil-proof agent; wherein the particle size of the multi-scale nano-lignin is 200-1500nm.
2. The method for preparing a multi-scale nano-lignin water-proof and oil-proof agent using alkaline pulping black liquor according to claim 1, characterized in that: The specific process of the acid precipitation method is: stirring and heating the alkaline pulping black liquor, adjusting the pH value of the solution with acid, standing and settling, centrifuging and washing to neutrality, freeze drying, grinding, and vacuum drying to obtain multi-scale nano lignin particles.
3. The method for preparing a multi-scale nano-lignin water-proof and oil-proof agent using alkaline pulping black liquor according to claim 2, characterized in that: The stirring speed is 100-1000 rpm, and the temperature is raised to 20-100°C.
4. The method for preparing a multi-scale nano-lignin water-proof and oil-proof agent using alkaline pulping black liquor according to claim 2, characterized in that: When the pH value of the adjusted solution is 1 to 5, stop adding acid and stir the mixture for 30 to 150 minutes.
5. The method for preparing a multi-scale nano-lignin water-proof and oil-proof agent using alkaline pulping black liquor according to claim 1, characterized in that: The starch is selected from any one of surface starch, native starch, oxidized starch and cationic starch.
6. The method for preparing a multi-scale nano-lignin water-proof and oil-proof agent using alkaline pulping black liquor according to claim 1, characterized in that: The mass ratio of the multi-scale nano-lignin to starch is 0.5 to 2:
2.
7. The method for preparing a multi-scale nano-lignin water-proof and oil-proof agent using alkaline pulping black liquor according to claim 1, characterized in that: The specific steps include: 1) mechanically stirring the alkaline pulping black liquor, adding acid dropwise while stirring until the pH value of the black liquor is 1-5, stopping the acid addition, keeping warm and continuing stirring, standing and settling, centrifugally washing to neutrality, freeze drying, grinding, and vacuum drying to obtain multi-scale nano-lignin particles; 2) The multi-scale nano-lignin particles prepared in step 1), starch and purified water are mixed and gelatinized to prepare a multi-scale lignin waterproof and oil-proof agent, and the mixture is kept warm at 60° C. for use.
8. The method for preparing a multi-scale nano-lignin waterproof and oil-proof agent using alkaline pulping black liquor according to any one of claims 1 to 7, wherein the multi-scale nano-lignin waterproof and oil-proof agent is prepared.
9. Use of the multi-scale nano-lignin waterproof and oil-proof agent according to claim 8 in the preparation of waterproof and oil-proof paper-based materials.
10. The use according to claim 9, characterized in that: The preparation process is as follows: Use a rod coater to coat the product with a weight of 80 g / m 2 Double coating is applied on the surface of A4 paper with a coating amount of 5g / m 2 First, apply a layer of multi-scale nano-lignin waterproof and oil-proof agent on the surface of the paper, put the paper with one layer into a 60℃ constant temperature oven for drying for 2 minutes and then take it out, apply the second layer of starch and put it into a 60℃ constant temperature oven for drying for 5 minutes, and finally let the treated A4 paper stand in a constant temperature and humidity room for 24 hours.
Citation Information
Patent Citations
Method for preparing lignin nanoparticles by taking papermaking black liquid as raw material
CN103275331A
Resource utilization method of lignin in formic-acid pulping waste liquid
CN109939569A
Method for improving water vapour and grease barrier property of food wrapper
CN110241658A
Production method of environment-friendly grease-resistant paper
CN112482090A
Lignin micro-nano particles prepared by using high-pressure homogenization method and application of lignin micro-nano particles
CN118546399A
Cited By
Preparation method of lignin nanoparticle liquid-phase dispersion or solid dispersion
CN121293538A